2017
DOI: 10.1371/journal.pone.0184174
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease and mortality after breast cancer in postmenopausal women: Results from the Women’s Health Initiative

Abstract: BackgroundCardiovascular disease (CVD) is the leading cause of morbidity and mortality among older postmenopausal women. The impact of postmenopausal breast cancer on CVD for older women is uncertain. We hypothesized that older postmenopausal women with breast cancer would be at a higher risk of CVD than similar aged women without breast cancer and that CVD would be a major contributor to the subsequent morbidity and mortality.MethodsIn a prospective Women’s Health Initiative study, incident CVD events and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 45 publications
3
55
0
6
Order By: Relevance
“…A recent systematic review examined the risk of CVD mortality after breast cancer, and concluded that approximately 2% to 10% of women with breast cancer die of CVD, and that CVD mortality is elevated among women with breast cancer compared with women without a breast cancer history . Similar to women in the general population, traditional risk factors for CVD, such as hypertension and excess adiposity, have been associated with CVD incidence and mortality among survivors of breast cancer . However, to our knowledge, whether breast cancer and its treatment exacerbate these risk factors, contributing to greater increases in CVD risk over time compared with among women without breast cancer, has not been well established to date.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review examined the risk of CVD mortality after breast cancer, and concluded that approximately 2% to 10% of women with breast cancer die of CVD, and that CVD mortality is elevated among women with breast cancer compared with women without a breast cancer history . Similar to women in the general population, traditional risk factors for CVD, such as hypertension and excess adiposity, have been associated with CVD incidence and mortality among survivors of breast cancer . However, to our knowledge, whether breast cancer and its treatment exacerbate these risk factors, contributing to greater increases in CVD risk over time compared with among women without breast cancer, has not been well established to date.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the most recent statistics available, 236 968 women were diagnosed with breast cancer in 2014 and 41 211 women died from breast cancer in the United States . The Surveillance, Epidemiology and End Results data and numerous other population studies have demonstrated an increased incidence in cardiovascular disease in breast cancer survivors, compared to other women without breast cancer …”
Section: Introductionmentioning
confidence: 99%
“…Advancements in early detection and breast cancer therapy have resulted in over 90% of women surviving 5 years past their diagnosis of breast cancer, with a related mortality reduction of ~2% per year over the last decade . Nonetheless, with increased survivorship from breast cancer there has been an increase in cardiovascular disease in these women . For breast cancer survivors, deaths due to cardiovascular diseases account for 35% of the non–cancer‐related deaths in those age 50 years and older, and cardiovascular mortality is the greatest single non–cancer‐related cause of death …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for cardiac monitoring during treatment, with underdiagnosis and undertreatment of cardiovascular disease (CVD) an important issue for patients with breast cancer . CVD is the leading cause of death for women worldwide ; among patients with breast cancer, CVD is a primary cause of death in women aged ≥75 years with stage I or localized disease . Seven years postdiagnosis, patients with breast cancer have nearly twice the risk of CVD‐related mortality compared with patients without a diagnosis of breast cancer .…”
Section: Introductionmentioning
confidence: 99%